Improvements of the Dressing Process of Super Abrasive Diamond Grinding Wheels - Kundrak, Janos; Fedorovich, Vladimir; Markopoulos, Angelos P.; Pyzhov, Ivan; Kryukova, Natalya (Manufacturing Technology Journal, 2014)
Grinding is the most common finishing process for components that require high accuracy and surface quality. Process performance depends on many factors related to process conditions, workpiece material, grinding fluid but grinding wheel is of special interest. Grinding wheel performance plays a major role on workpiece quality and process efficiency; preparation of the grinding tools and the creation of specific topography of the wheel surface is in direct relation to grinding wheel performance. Questions connected to the possibility to increase production efficiency of diamond dressers owing to technological changes of their production and simplification of preliminary selection of initial samples of diamond are considered. Furthermore, recommendations on improvement of the dressing process of abrasive wheels are made using 3D FEM simulations. The results of theoretical and experimental investigations which cover the development and research on electrochemical dressing of working surface of diamond grinding wheels with metal bonds are also provided.
Keywords: diamond dresser; abrasive ability; wheel dressing; 3D simulation; metal bond of grinding wheels